Education and Human Resource Development with Neuro-Linguistic Programming (NLP) Techniques: A Case Study of Muhammad Al-Fatih's Leadership - Salamun, Salamun; Masrur, Moh. (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2024)
Education and human resource development (HR) play an important role in achieving individual and organizational success, with Neuro-Linguistic Programming (NLP) as an effective technique to achieve positive change. This study analyzes the application of NLP in the context of education and human resource development through the case study of Muhammad Al-Fatih, the visionary leader and conqueror of Constantinople. This research highlights how NLP principles, such as mind control, communication mastery, and goal design, are applied in the leadership and educational strategies that shape the character of Al-Fatih. Qualitative methods with a historical approach are used to analyze primary and secondary sources related to Al-Fatih's life. The results of the study show that NLP plays an important role in the formation of character and the development of its competencies, with the application of these techniques in education, such as vision and motivation coaching, contributing to its success. This study recommends the integration of NLP in modern educational curricula to produce resilient, adaptive, and visionary human resources.